2019
DOI: 10.1002/ncp.10444
|View full text |Cite
|
Sign up to set email alerts
|

Using Global Criteria to Detect Malnutrition: Application in Disease States

Abstract: The accurate diagnosis and subsequent treatment of malnutrition is an essential component of nutrition care because of the known negative impacts of malnutrition on patient outcomes. The detection of malnutrition is influenced by disease-specific characteristics, practice settings, and the availability of resources. This article explores how malnutrition diagnosis through the application of the Global Leadership Initiative on Malnutrition global consensus on malnutrition diagnostic criteria is impacted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
0
10
0
2
Order By: Relevance
“…Nutrition is important for the patients with advanced malignancy to receive chemotherapy. PG-SGA currently is the standard of patient assessment in oncology and other chronic catabolic condition [31]. In this study, the scores of PG-SGA were correlated to therapeutic responses of ICI.…”
Section: Discussionmentioning
confidence: 89%
“…Nutrition is important for the patients with advanced malignancy to receive chemotherapy. PG-SGA currently is the standard of patient assessment in oncology and other chronic catabolic condition [31]. In this study, the scores of PG-SGA were correlated to therapeutic responses of ICI.…”
Section: Discussionmentioning
confidence: 89%
“…Similar effect was observed in acute pancreatitis patients, and the nutritional status of patients was also improved ( 23 ). Distinctive and complex metabolic changes after trauma make severe trauma patients more susceptible for developing malnutrition ( 6 , 24 ). One review further indicated that depending on the severity of injury, energy expenditure increased by 20–50% in trauma patients compared with patients after elective surgery ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…190 Las herramientas de tamizaje validadas son: Nutritional Risk Screening 2002 (NRS-2002), Malnutrición Universal Screening Tool (MUST), Mini-Nutritional Assessment (MNA) en su forma completa o corta (MNA-SF), Malnutrición Screening Tool (MST) y Short Nutritional Assessment Questionnaire (SNAQ). 183,[191][192][193] La herramienta más adecuada es aquella que sea fácil de realizar, sensible a los cambios agudos y crónicos del Figura 1.…”
Section: Evaluación Y Requerimientos Nutricionalesunclassified